Role of CTA in Women with Abdominal Scars Undergoing DIEP Breast Reconstruction: Review of 1,187 Flaps - Daly, Lauren T.; Doval, Andres F.; Lin, Samuel J.; Tobias, Adam; Lee, Bernard T.; Dowlatshahi, A. Samandar (Journal of Reconstructive Microsurgery, 2020)
Background This study examines the effect of prior abdominal surgery on flap, donor-site, and overall complications in women undergoing deep inferior epigastric artery perforator (DIEP) flap breast reconstruction and assesses whether preoperative computed tomography angiography (CTA) affects outcomes.Methods All DIEP flaps performed at our institution between 2004 and 2015 were identified retrospectively. Patients were stratified based on a history of prior abdominal surgery and whether or not they underwent a preoperative CTA. A subgroup analysis was performed to compare operative times and incidence of complications using adjusted odds ratios (ORs).Results Over a 12-year period, 425 patients (640 flaps) had prior abdominal surgery, and 393 patients (547 flaps) had no prior abdominal surgery. Of the patients with previous abdominal surgery, 67 (15.7%) underwent preoperative CTA and 333 (78.4%) did not. Patients with prior abdominal surgery were more likely to have donor-site wound complications (OR: 1.82, 95% confidence interval [CI]: 1.15–2.87, p = 0.01), fat necrosis ≥2cm of the transferred flap (OR: 1.39, 95% CI: 1.0–1.94, p = 0.05), and were more likely to have bilateral DIEP flap reconstruction (OR: 1.61, 95% CI: 1.22–2.12, p < 0.001). Preoperative CTA did not reduce the risk of complications and did not affect operative times.Conclusion DIEP flap reconstruction can be safely performed in women with prior abdominal surgery. However, these patients should be counseled that they are at an increased risk for donor-site wound breakdown and fat necrosis of the reconstructed breast. Preoperative CTA does not reduce complication rate, overall operative time, or time needed to dissect perforators in women with abdominal scars.
Keywords: breast reconstruction; DIEP flap; patient outcomes